The Influence of Parenting and Peer Groups to Social Capital - Lili Dianah (Institut Pendidikan Indonesia, 2022)
AbstractThis study aims to measure and analyze the effect of parenting patterns of parents and peer groups on social capital. This study uses a quantitative approach and survey methods. The research sample consisted of 400 respondents from 16 public junior high schools in West Bandung Regency. The sample that became the object of the study was made up of 8th-grade students. The sample was drawn using stratified random sampling. The results showed that the parenting patterns of parents and peer groups had a positive and significant effect on students' social capital. Parenting patterns influence social capital by 20%. Social capital has a 25% influence. Taken together, the parenting styles of parents and peer groups influence capital by 47% and social impact by 53%, after the influence of other factors. Peer group characteristics had the most impact on social capital in this study. The inference is that enlarging a student's peer group can boost their social capital. Keywords: Parenting Patterns of Parents, Peer Group, Social Capital AbstrakPenelitian ini bertujuan untuk mengukur dan menganalisis pengaruh pola asuh orang tua dan kelompok teman sebaya terhadap modal sosial. Penelitian ini menggunakan pendekatan kuntitatif dan metode survai. Sampel penelitian sebanyak 400 responden dari 16 SMP Negeri di Kabupaten Bandung Barat. Sampel yang menjadi objek penelitian adalah siswa kelas 8. Penarikan sampel dilakukan secara Stratified random sampling. Hasil penelitian menunjukkan bahwa pola asuh orang tua dan kelompok teman sebaya berpengaruh positif dan signifikan terhadap modal sosial siswa. Pola asuh orang tua memiliki pengaruh terhadap modal sosial sebesar 20%. Kelompok teman sebaya memiliki pengaruh terhadap modal sosial sebesar 25%. Secara bersama-sama, pola asuh orang tua dan kelompok teman sebaya ini memiliki pengaruh terhadap modal sosial siswa sebesar 47% dan sisanya 53% dipengaruhi faktor lain. Dalam penelitian ini variabel kelompok teman sebaya memiliki pengaruh paling besar terhadap modal sosial. Implikasinya bahwa modal sosial siswa dapat ditingkatkan dengan meningkatkan kelompok teman sebaya. Kata Kunci: Pola Asuh Orangtua, Kelompok Teman Sebaya, Modal Sosial.